Hellénisme et patristique grecque: continuité et discontinuité - Dorival, Gilles (Antigüedad y Cristianismo, 1990)
The way in which took place the meeting between the Helenism and the Christianity of the Greek Fathers has provoked contradicting opinions: conflict and antagonism, o continuity and ajustments? Actually one could say that the Greek Patristic is at the same time a continuity and a discontinuity of the Hellenism, as has been shown by the studies of the methodology, of the literary forms, of the rhetoric, of the theology and of the patristic values.